Avaliação dos efeitos genotóxicos e antigenotóxicos de Salvia officinalis e seus aspectos terapêuticos em ciência animal - TERRA, Roberta Soares (2017)
Salvia officinalis has been widely used in culinary and traditional medicine, and studies have identified numerous chemical compounds and potential therapeutic actions. This study evaluated the genotoxicity of lyophilized hydroalcoholic extract of S. officinalis L. (SO) leaves using the micronucleus assay in mouse bone marrow. The interaction between SO and the genotoxic effects induced by doxorubicin (DXR) was also analyzed – antigenotoxicity assay. Experimental groups consisting of male and female Swiss albinus mice (Unib: SW) were evaluated after 24-48h treatment with cyclophosphamide (CP; 50 mg/kg), DXR (5 mg/kg), NaCl 0.5-2 g/kg) and SO (0.5 g/kg) + DXR (5 mg/kg). The PCEMN analyzes showed differences (p0.05) between SO (1-2 g/kg) and NaCl treatments, regardless of gender and time. DXR induced EPCMNs significantly in both genders and treatment times. Groups of mice treated with DXR showed lower frequencies (p0.05) of PCEMNs when compared to CP control groups (50 mg/kg). Associative treatment (500 mg/kg SO + 5 mg/kg DXR) did not reduce the frequency of DXR-induced PCEMNs (p0.05). The PCE/NCE ratio between control (NaCl, CP and DXR) and experimental genotoxic and antigenotoxic (SO; SO + DXR) treatments were insignificant (p0.05). The results suggest moderately genotoxic effects (clastogeny and/or aneugeny) of S. officinalis L. leaves, dose-dependent (i.e., from 1 g/kg) and gender- and time-independent. However, S. officinalis has no systemic toxicity and antigenotoxic effects (SO + DXR) under the conditions established in the present micronucleus test in mouse bone marrow.